Textual warfare and the making of methodism - McInelly, Brett C. (Oxford University Press, 2014)
Print culture and the making of Methodism -- Rhetoric and revival -- Performing the revival -- Hymn singing, the anti-Methodist response, and the revival -- Sexualized spirituality, sexual politics, and the revival -- Methodist infighting and the revival